2015
DOI: 10.1128/jcm.03679-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Two PCR-Based Methods for Detection of Methicillin-Resistant Staphylococcus aureus (MRSA): Xpert MRSA Gen 3 and BD-Max MRSA XT

Abstract: We compared two walk-away molecular diagnostic assays, the GeneXpert MRSA Gen 3 assay and the BD-Max MRSA XT assay. A total of 119 prospective swabs and 36 culture-positive samples were tested. Xpert MRSA Gen 3 had sensitivity of 95.7% and specificity of 100% versus 87.5% and 97.1% for BD-Max. The difference in agreement with the enriched culture results was significantly in favor of the Xpert assay (P < 0.02, McNemar nonparametric text).T he transmission of methicillin-resistant Staphylococcus aureus (MRSA) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
(18 reference statements)
1
9
0
Order By: Relevance
“…All 98 MSSA strains tested showed negative results for mecAmecC amplification (100% negative agreement) and hence were correctly categorized as MSSA (see Table S1 in the supplemental material), similar to in a recent prospective study (23). Twentyseven MSSA strains showed positive results in SCCmec-orfX junction testing, including those previously characterized as SCCmec remnant strains, and eight of the 10 isolates tested false positive in the previous version of the Xpert MRSA PCR assay (see Table S1).…”
supporting
confidence: 48%
“…All 98 MSSA strains tested showed negative results for mecAmecC amplification (100% negative agreement) and hence were correctly categorized as MSSA (see Table S1 in the supplemental material), similar to in a recent prospective study (23). Twentyseven MSSA strains showed positive results in SCCmec-orfX junction testing, including those previously characterized as SCCmec remnant strains, and eight of the 10 isolates tested false positive in the previous version of the Xpert MRSA PCR assay (see Table S1).…”
supporting
confidence: 48%
“…The new assay, GeneXpert MRSA Gen 3, was also updated to detect SCCmec VI-XI, on top of the I-V that it previously detected. A study by Lepainteur et al (2015) detecting MRSA directly from nasal swabs showed that the assay had a sensitivity of 95.7% and a specificity of 100%. The BD Max MRSA XT (extended detection technology) kit was also introduced to detect mecC as well as mecA and, in the same study by Lepainteur, was shown to have a sensitivity and specificity of 87.5 and 97.1% respectively (Lepainteur et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, any emerging variant SCCmec new types will not be detected. In recent years these assays have been updated to improve sensitivities and specificities, and to include the mecA/C genes, such as with the BD Max MRSA XT, Xpert gen3, and BD Max StaphSR assays (Ellem et al, 2015;Lepainteur et al, 2015;Silbert et al, 2015Silbert et al, , 2017Becker et al, 2016;Mendes et al, 2016). They still, however, rely on detection at the SCCmec-orfX junction and could suffer from the lack of ability to detect emerging SCCmec variants.…”
Section: Introductionmentioning
confidence: 99%
“…These results corroborate evidence about wrong identification or misidentification of MRSA described by some colleagues (16)(17)(18)(19)(20)33) and demonstrate an improvement of the new-generation BD Max MRSAXT and BD Max StaphSR assays to correctly identify or exclude these strains. A recent study from Europe reports the performance of the Xpert MRSA Gen3 assay, which also detects mecA/mecC and the SCCmec/orfX junction for MRSA (34).…”
Section: Discussionmentioning
confidence: 99%